Potential of lignocellulosic biomass applied to Carbon Dioxide (CO2) capture - Costa, Naiara Lima; Camargo, Júnior da Silva; Souza , Dener da Silva; Silva, Michael Jones da (Technical and Scientific Journal Green Cities, 2025)
Objective – The objective of this study is, through a systematic literature review, to analyze the contribution of lignocellulosic biomass in carbon dioxide (CO2) capture, as well as to identify the main influencing factors assessed in related research. Methodology – The study used the PRISMA methodology (Preferred Reporting Items for Systematic reviews and Meta-Analyses). In the investigation, the terms "lignocellulosic biomass," "carbon dioxide," and "adsorption" were used concurrently and directed to the title, abstract, and keywords of the studies. The selected papers were published between 2020 and 2024 and do not include review articles. Originality/Relevance – Driven by increasingly evident climate changes, it is essential that renewable natural resources, and especially the waste from these resources, be studied and promoted as biomaterials aimed at uses with the potential to mitigate Greenhouse Gas (GHG) emissions. Multiple biomasses have characteristics favorable for the adsorption of various substances, and given the vast number of species with diverse traits, it is necessary to evaluate their main contributions. Furthermore, the evaluation of biochars from biomass waste leads to the valorization of the product, with low associated costs and fostering innovation. Results – The studies highlight the high adsorption capacity of different biomasses, enhanced by activation processes or other treatments. Furthermore, the influences of temperature and pressure on the process are emphasized, demonstrating the pathways that are favored. Theoretical/Methodological Contributions – The factors that influence the applicability of a material, especially that of a renewable resource waste, are fundamentally important for understanding the effectiveness of processes and their laboratory or commercial reproduction. Temperature and pressure directly affect the efficiency of processes, and the activation of a biochar depends directly on the methodology used, which influences its adsorption capacity. Systematic literature reviews provide a consolidated synthesis of practices and approaches, demonstrating trends and predominantly used assessments, allowing for the use of efficient methodologies. Social and Environmental Contributions - The study highlights the contributions in recent literature regarding lignocellulosic biomasses in carbon capture, the primary gas responsible for the greenhouse effect. Given that Brazil is one of the most biodiverse countries and has a large production of various plant materials, it is important to understand waste as potential materials in the fight against mitigation.